2013
DOI: 10.1149/05009.0875ecst
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Properties and Strain Relaxation Mechanism of CVD Grown GeSn

Abstract: The crystalline properties of strained and strain-relaxed CVDgrown GeSn layers were investigated. A positive deviation from Vegard's law was determined, resulting in the extraction of a new experimental bowing parameter for GeSn: b GeSn = 0.041 Å (in excellent agreement with recent theoretical predictions). The GeSn critical thickness for strain relaxation as a function of Sn concentration was determined, resulting in significantly higher values than those predicted by equilibrium models. A composition-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…However, we also observed that when the thickness of these layers increases, their surface is increasingly covered by islands, which we initially attributed to strain relaxation [7]. In this work, we investigate in more details the characteristics of these islands and we discuss the presence of an amorphous core inside them.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, we also observed that when the thickness of these layers increases, their surface is increasingly covered by islands, which we initially attributed to strain relaxation [7]. In this work, we investigate in more details the characteristics of these islands and we discuss the presence of an amorphous core inside them.…”
Section: Introductionmentioning
confidence: 81%
“…Low temperature growth processes are often required in order to fabricate Ge or GeSn heterostructures without undesired strain relaxations, elemental intermixing, dopant diffusion or Sn precipitation [5]. However, low-temperature growth is known to have a series of possible undesired consequences, such as the roughening of the surface [6], the formation of defects or the inclusion of localized or extended amorphous regions [6][7][8] (often referred to as epitaxial breakdown).…”
Section: Introductionmentioning
confidence: 99%
“…In theory, these materials can be used to achieve a direct energetic transition in a lattice-matched heterostructure grown on a Si substrate [1][2]. Even though the lattice mismatch between Ge and Sn is large, recent progress in growth has been reported, showing the realization of a fully strained Ge 0.92 Sn 0.08 layer on Ge [3][4]. This technological development allows evaluating the emission and absorption properties of these lattice-matched heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The peak of the roughly 2.5 µm thick Ge buffer lies below the cubic lattice line indicating a weak tensile strain of 0.16 %, whereas the GeSn peak is on the pseudomorphic line, proving that its growth was pseudomorphic on the Ge-VS underneath. A large compressive strain of about -1.9 % is obtained by using the bowing corrected Vegard´s law [8]. Room temperature photoluminescence measurements of these highly strained layers are presented in Fig.…”
Section: Methodsmentioning
confidence: 99%